Modifying the progression of Alzheimer's and Parkinson's disease with deep brain stimulation - Jakobs, Martin; Lee, Darrin J.; Lozano, Andres M. (Neuropharmacology, 2020)
At times of an aging population and increasing prevalence of neurodegenerative disorders, effective medical treatments remain limited. Therefore, there is an urgent need for new therapies to treat Alzheimer's disease (AD). Deep brain stimulation (DBS) is thought to address the neuronal network dysfunction of this disorder and may offer new therapeutic options. Preliminary evidence suggests that DBS of the fornix may have effects on cognitive decline, brain glucose metabolism, hippocampal volume and cortical grey matter volume in certain patients with mild AD. Rodent studies have shown that increase of cholinergic neurotransmitters, hippocampal neurogenesis, synaptic plasticity and reduction of amyloid plaques are associated with DBS. Currently a large phase III study of fornix DBS is assessing efficacy in patients with mild AD aged 65 years and older. The Nucleus basalis of Meynert has also been explored in a phase I study in of mild to moderate AD and was tolerated well regardless of the lack of benefit. Being an established therapy for Parkinson's Disease (PD), DBS may exert some disease-modifying traits rather than being a purely symptomatic treatment. There is evidence of dopaminergic neuroprotection in animal models and some suggestion that DBS may influence the natural progression of the disorder. Neuromodulation may possibly have beneficial effects on course of different neurodegenerative disorders compared to medical therapy alone. For dementias, functional neurosurgery may provide an adjunctive option in patient care. This article is part of the special issue entitled ‘The Quest for Disease-Modifying Therapies for Neurodegenerative Disorders’.
Available online 23 November 2019
Gesehen am 03.07.2020